The Implications of the Application of the Hannafin and Pack Learning Model on Student Learning Outcomes in Learning Islamic Religious Education at SDN Sukamantri, Cileunyi District, Bandung Regency - Mulyati, Yanti; Nugraha, Mulyawan Safwandy; Dedih, Ujang (Edumaspul: Jurnal Pendidikan, 2024)
This paper examines the implications of implementing the Hannafin and Pack learning model on student learning outcomes in Islamic Religious Education learning at SDN Sukamantri, Cileunyi District, Bandung Regency. The learning model is one of the key factors for teacher success in improving student learning outcomes. Therefore, every teacher is required to be able to develop the Hannafin and Pack learning model in Islamic Religious Education learning so that students’ level of development, knowledge, and learning outcomes increase. This research uses descriptive methods and a quantitative approach. The technique and collection of the data sources refer to the results of empirical observations, interviews with respondents, and relevant book reviews. The results of this research show that the application of the Hannafin and Pack learning model has proven to have positive implications for increasing student learning outcomes in Islamic Religious Education subjects at SDN Sukamantri, Cileunyi District, Bandung Regency with a learning outcome level of 87% (good category). The implication of this research is every teacher needs to use various models, strategies, methods, approaches and learning techniques in Islamic Religious Education subjects so that student learning outcomes increase.